Burden of upper gastrointestinal symptoms in patients prescribed dabigatran for stroke prevention. (3rd August 2016) - Chan, Pak-Hei; Hai, Jo-Jo; Huang, Duo; Ho, Mei-Han; Chan, Esther W; Cheung, Bernard Man-Yung; Chan, Annie On-On; Wong, Ian Chi-Kei; Tse, Hung-Fat; Hung, Ivan Fan-Ngai; Siu, Chung-Wah
Background: Dabigatran, a non-vitamin K antagonist oral anticoagulant, has been shown to prevent stroke in patients with non-valvular atrial fibrillation. Nonetheless, studies show that 10%–30% of those prescribed dabigatran experience dyspepsia that may eventually lead to discontinuation of therapy and loss of clinical benefit. Aim: To evaluate the gastrointestinal tolerability of dabigatran utilizing a validated questionnaire, as well as determining subsequent non-compliance and drug discontinuation. Method: This is an observational study. All patients were assessed by a validated questionnaire, Hong Kong dyspepsia index, prior to drug prescription and again 4 weeks later. Results: In this study, 115 patients with non-valvular atrial fibrillation (mean age: 74.6 ± 11.4 years; mean CHA2 DS2 -VASc score was 3.39 ± 1.59) were prescribed dabigatran. At baseline, the mean Hong Kong dyspepsia index was 12.9 ± 1.6 and nine patients had significant dyspepsia (Hong Kong dyspepsia index ⩾ 16). After 4 weeks, the mean Hong Kong dyspepsia index was similar at 12.6 ± 1.9 ( p  = 0.23). There was no change in Hong Kong dyspepsia index after initiation of dabigatran in 59 (51.3%) patients, and improvement in 37 (32.2%). Only 19 (16.5%) patients had worsening of Hong Kong dyspepsia index, and among these 19 patients, only 1 patient (0.9%) discontinued dabigatran due to significant dyspepsia. Conclusion: Worsening of dyspepsia with dabigatran 110 mg twice daily was uncommon with correct drug administration and clear instructions provided. Systematic assessment of dyspeptic symptoms using a validated questionnaire (i.e. Hong Kong dyspepsia index) before and after treatment initiation allows a more objective comparison of dyspeptic symptoms.